Theoretical and experimental studies on theophylline release from hydrophilic alginate nanoparticles - Deepa Thomas; Vinish V. Nair; M. S. Latha; K. Kurien Thomas (SpringerOpen, 2019)
Abstract Background Mathematical modelling may be able to reduce the number of in vitro experiments and provide an insight into the elementary physical and chemical mechanisms that regulate the rate and degree of drug release. The aim of the present examination was to develop a simple mathematical model to portray drug release from the alginate-type hydrophilic matrix, taking into account the Fickian diffusion of drug and swelling of the matrix using theophylline as the model drug. Results The nanoparticles show a remarkable swelling in the simulated intestinal fluid. The theoretical drug release values were validated with experimental values by considering diffusion and diffusion with swelling. The experimental value fitted well with the theoretical value predicted based on diffusion. It was found that after 3 h, the entire drug release followed a pure diffusion transport. Conclusions The numerical model was found to be sufficiently accurate in guessing the drug release from the alginate matrix. The developed model could be extended to quantitatively prognosticate the drug release from hydrophilic spherical matrices.